2009
DOI: 10.1091/mbc.e08-10-1019
|View full text |Cite
|
Sign up to set email alerts
|

Trf1 Is Not Required for Proliferation or Functional Telomere Maintenance in Chicken DT40 Cells

Abstract: The telomere end-protection complex prevents the ends of linear eukaryotic chromosomes from degradation or inappropriate DNA repair. The homodimeric double-stranded DNA-binding protein, Trf1, is a component of this complex and is essential for mouse embryonic development. To define the requirement for Trf1 in somatic cells, we deleted Trf1 in chicken DT40 cells by gene targeting. Trf1-deficient cells proliferated as rapidly as control cells and showed telomeric localization of Trf2, Rap1, and Pot1. Telomeric G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
1
15
1
Order By: Relevance
“…Using the siRNA technique, we have confirmed that high levels of TRF2 downregulation induce apoptosis and low levels of TRF2 downregu- lation induce senescence, and we also found that the selective knockdown of TRF1 induces neither senescence nor apoptosis. These results are in agreement with a number of studies finding that a dominant negative allele of human TRF1 does not affect the growth and viability of a variety of primary and transformed human cells (12,25,26,55).…”
Section: Different Doses Of Doxorubicin Induce Senescence or Apoptosisupporting
confidence: 93%
“…Using the siRNA technique, we have confirmed that high levels of TRF2 downregulation induce apoptosis and low levels of TRF2 downregu- lation induce senescence, and we also found that the selective knockdown of TRF1 induces neither senescence nor apoptosis. These results are in agreement with a number of studies finding that a dominant negative allele of human TRF1 does not affect the growth and viability of a variety of primary and transformed human cells (12,25,26,55).…”
Section: Different Doses Of Doxorubicin Induce Senescence or Apoptosisupporting
confidence: 93%
“…Although there are many properties of cells that are affected by the passaging process [21,31,36,45,88,95,99,129], we choose to focus on how passaging affects the cell proliferation rate. In our model, when a cell proliferates, the daughter cells directly inherit the same proliferation rate as the mother cell.…”
Section: Discussionmentioning
confidence: 99%
“…During the passaging process, cells are lifted, split into smaller proportions, and re-grown in new cell culture flasks [8,9]. It is reported that cell characteristics change at high passage numbers, and seemingly contradictory effects have been observed in experiments of passaging cell lines [21,31,45,73,88,95,99]. For example, many studies report that cell proliferation decreases with the increasing passage number [31,45,95,99], whereas Lin et al find that cell proliferation increases at high passage numbers [73].…”
Section: How Does Cell Proliferation Change At High Passage Numbers? mentioning
confidence: 99%
See 2 more Smart Citations